ANALISIS PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI PEMERSATU BANGSA - Rofiq, Ainur; Muqfy, Hasanul (Managere: Indonesian Journal of Educational Management, 2019)
This multicultural education is likened to a bridge to achieve life together with humanity in this globalization era full of challenges. The main purpose of multicultural Islamic education is to emphasize the whole environment or educational atmosphere, so that multicultural Islamic education can increase respect or attention to cultural groups that are very broad or different to get the same education, which is equal to most people in general. This research uses the library method by analyzing data from relevant journals and books. The results of this study indicate that multicultural education must be applied in various lines of education especially conflict prone areas.